Prophecy and the battle for spiritual authority, 1360-1400: outsiders, women, and reformers - Kneupper, Frances Courtney (Oxford scholarship online, 2025)
The end of the fourteenth century was a time of upheaval and contested authority among the traditional institutions of medieval Europe. In response to these conditions, a number of people began to claim their own authority, as prophets speaking the word of God. They came from outside of the clerical elite and were mostly women and reformers. This book examines the battle over authority which ensued